2000
DOI: 10.1097/00055735-200004000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing modulation after glaucoma surgery

Abstract: Recent developments in molecular and cell biology have made a major impact on our understanding of the wound healing process and its modification. In this article, the spectrum of therapies that are either currently available or have potential application as modulators of the scarring response following glaucoma surgery are reviewed. Refinement of existing antimetabolite regimens can improve surgical results, especially in carefully selected patient groups. However, the most promising new approach appears to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…In this paper, we found that Bevacizumab not only effects VEGF and its receptors expression but also reduces TGFb. TGFb is a key mediator of inflammation and critically involved in postoperative scarring [26,27]. Interestingly, recent study showed that VEGF induced TGF-b1 expression and myofibroblast transformation after glaucoma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we found that Bevacizumab not only effects VEGF and its receptors expression but also reduces TGFb. TGFb is a key mediator of inflammation and critically involved in postoperative scarring [26,27]. Interestingly, recent study showed that VEGF induced TGF-b1 expression and myofibroblast transformation after glaucoma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, expression of TGFb1 and TGFb2 in fibroblast was also inhibited by Bevacizumab. It has been reported that VEGF had a critical role in TGF-b1 production and may result in excessive fibrosis by activating myofibroblast transformation in various diseases [21][22][23][24]. Especially, VEGF was found that it could induce TGF-b1 in the subconjunctival tissue, resulting in excessive subconjunctival fibrosis after trabeculectomy [25].…”
Section: Discussionmentioning
confidence: 99%
“…The main problem with all filtering procedures remains subconjunctival scarring caused by increased postoperative fibroblast activity [1,3,21,25]. This phenomenon occurs regularly after ab-externo laser sclerostomy, regardless of surgical modifications, the laser wavelength, and total energy used [7,8,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, our surgical modification does not solve the key problem of episcleral scarring, as subconjunctival drainage still occurs. As the rabbit eye usually shows accelerated scar formation after any filtering procedure, we performed a short-term study of only 14 days with a fixed ending, including the characteristic period of bleb closure [3,25].…”
Section: Discussionmentioning
confidence: 99%